Emotions, democracy and motivation. A critical reading of patriotism in Nussbaum (Estudios Sociales, 2019)
In this article I will analyze some aspects of Martha Nussbaum’s theory of political emotions and I will offer an interpretation of the problem of motivation and its links with those emotions. I will argue for two claims: i) Nussbaum’s approach to the problem of motivation can be explained with the concept of narration, and ii) her motivational model is closer to those externalists and Aristotelians discussed in the contemporary Metaethics. I will focus on her work on patriotism as it appears in his book, Political Emotions. Why Love Matters for Justice.